Structural and optical properties of Fe-doped SnO2 quantum dots. (12th December 2017) - Thirumala Rao, G; Babu, B; Ravikumar, R V S S N; Shim, Jaesool; Venkata Reddy, Ch
Abstract: Fe-doped SnO2 quantum dots (QDs) were synthesized by a time-efficient solution combustion synthesis with various concentration of Fe ions. The structural and optical properties are keenly investigated through various characterization techniques like XRD, HR-TEM, XPS, UV–vis, EPR, and FT-IR spectroscopies. The structural description gives an information that the SnO2 QDs are having a particle size below 5 nm with the tetragonal crystal structure. The Fe doping increases the absorption capability of SnO2 QDs via tuning of the bandgap. The bandgap of SnO2 QDs is decreased with increasing the content of Fe. The XPS study clearly confirms the existence of Fe in 3+  state as octahedral sites in SnO2 QDs which was further strongly supported by EPR. The FT-IR analysis gives the information of Fe doping effect on vibrational modes of SnO2 .